2002
DOI: 10.1124/mol.62.6.1492
|View full text |Cite
|
Sign up to set email alerts
|

Analogs of WIN 62,577 Define a Second Allosteric Site on Muscarinic Receptors

Abstract: WIN 51,pyrimido [1,2-a] 3 H]NMS dissociation from M 3 receptors indicate that PG987 binds reversibly to a site distinct from that to which gallamine and strychnine bind: in contrast, PG987 seems to bind to the same site on M 3 receptors as KT5720, staurosporine, and WIN 51,708. Therefore, in addition to the allosteric site that binds strychnine (and probably chloromethyl brucine, another allosteric enhancer) there is a second, nonoverlapping, pharmacologically distinct allosteric site on M 3 receptors that als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 23 publications
(27 reference statements)
1
95
0
Order By: Relevance
“…This finding is in general agreement with our prior mutagenesis study (Chan et al, 2008), which suggested an engagement of the modulator with extracellular loop regions of the M 4 mAChR and an important function of D 432 in the third extracellular loop; this residue has been implicated in the binding of the prototypical modulator, gallamine, to the M 4 mAChR (Gnagey et al, 1999). In contrast, the interaction between LY2033298 and atropine was negatively cooperative, whereas that between LY2033298 and WIN51708 was neutrally cooperative; both findings clearly indicate that LY2033298 does not interact with either the orthosteric site or a second allosteric site on the M 4 mAChR recognized by staurosporine, KT5720, and various WIN compounds (Lanzafame et al, 2006;Lazareno et al, 2000Lazareno et al, , 2002.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This finding is in general agreement with our prior mutagenesis study (Chan et al, 2008), which suggested an engagement of the modulator with extracellular loop regions of the M 4 mAChR and an important function of D 432 in the third extracellular loop; this residue has been implicated in the binding of the prototypical modulator, gallamine, to the M 4 mAChR (Gnagey et al, 1999). In contrast, the interaction between LY2033298 and atropine was negatively cooperative, whereas that between LY2033298 and WIN51708 was neutrally cooperative; both findings clearly indicate that LY2033298 does not interact with either the orthosteric site or a second allosteric site on the M 4 mAChR recognized by staurosporine, KT5720, and various WIN compounds (Lanzafame et al, 2006;Lazareno et al, 2000Lazareno et al, , 2002.…”
Section: Discussionmentioning
confidence: 54%
“…Preliminary mutagenesis experiments with LY2033298 also implicated extracellular loop regions in the actions of the modulator (Chan et al, 2008). However, there is another class of 'atypical' modulators, such as WIN51708, WIN62577, staurosporine, and KT5720, that bind to a second, currently unresolved, allosteric site on mAChRs (Lanzafame et al, 2006;Lazareno et al, 2000Lazareno et al, , 2002. Thus, to gain more definitive insight into which allosteric site is involved in the binding of LY2033298, we exploited the ability of the modulator to also act as an agonist and performed functional interaction studies between this compound and either the classic orthosteric antagonist, atropine, the 'prototypical-site' allosteric modulator, C 7 /3-phth, or the 'second-site' allosteric modulator, WIN51708.…”
Section: Ly2033298 Potentiates Both the Affinity And The Efficacy Of mentioning
confidence: 99%
“…In radioligand binding assays: (a) LY2033298 exhibited a lack of significant affinity modulation of the muscarinic orthosteric antagonists NMS and QNB (3-quinuclidinyl benzilate), indicating no overlap with the orthosteric binding site In [ 35 S]GTPγS binding assays: (b) coaddition of the mAChR antagonist atropine caused a substantial reduction in the maximal effect of LY2033298 with a minimal change in potency, characteristic of noncompetitive negative cooperativity (c) LY2033298 demonstrated a competitive interaction with the mAChR negative allosteric modulator C 7 /3-phth, known to bind the "common" muscarinic allosteric site 79 (d) LY2033298 exhibited neutral cooperativity upon coaddition with WIN51708, a known "second allosteric site" mAChR ligand, 73 confirming the allosteric agonist's site of action to be the "common" allosteric site on the M 4 mAChR The Prospect of Bitopic Interactions. While the M 1 mAChR-selective ligand literature reviewed herein provides substantial evidence to suggest purely allosteric modes of action, there exist several examples where this evidence is inconclusive.…”
Section: ■ Important Considerations In Allosteric Ligand Classificatimentioning
confidence: 99%
“…Theoretically, the EC 50 or IC 50 of the affinity ratio plot corresponds to the K d of the test agent at the free receptor, and the asymptotic level corresponds to the cooperativity constant for the test agent and primary ligand (Lazareno and Birdsall, 1995). Affinity ratios were calculated from the specific binding data as follows (Lazareno and Birdsall, 2000;Lazareno et al, 2002):…”
Section: Methodsmentioning
confidence: 99%